Pelatihan Peningkatan Kemampuan Anggota Palang Merah Remaja Dalam Penanganan Kejadian Kecelakaan Sehari Hari Di SMP N 6 Unggul Lahat Selatan Kabupaten Lahat Tahun 2022: Training to Increase the Capacity of Youth Red Cross Members in Handling Daily Accidents at SMP N 6 Unggul Lahat Selatan Lahat Regency in 2022 - Kamesyworo, Kamesyworo; Haryanti, Eka; Hartati, Sri (Jurnal Abdi Keperawatan dan Kedokteran, 2023)
The ultimate goal of every development is to improve the quality of Human Resources (HR). Human resources are both the subject and the object of development, covering the entire cycle of human life, from the womb to the end of life. Therefore, the development of human quality must be an important concern. Based on the cycle above, it is necessary to have an effort to provide alternative solutions that can increase the Knowledge and Skills of Youth Red Cross (PMR) members in handling cases of daily accidents that occur in schools, especially in SMP N 1 Lahat Selatan. There is a transfer of knowledge and skills with emergency training on daily accidents that occur in schools for members of the Youth Red Cross as community partners. This training aims to provide the ability for Youth Red Cross Members to provide first aid to everyday accidents that occur in the school environment. The target for this training is the 24 members of the Youth Red Palan. The method of activity that will be used is the training for Handling Patients with Daily Accidents which often occur in the school environment. Participants will be given material on the concept of First Handling in Accidents, Stopping bleeding and splinting, Airway Obstruction and how to overcome it. From the results of the training carried out at SMP N I Lahat Selatan, it was found that before the intervention was carried out there were 45% of students who had good knowledge, after the intervention was carried out there was an increase of 79.2% of students who had good knowledge, the rest was sufficient. The outputs obtained from this activity are that members of the Youth Red Cross are able to understand whatthey do when they find victims with everyday accidents that occur at school.